Sexual Dimorphism in Abdominal Aortic Aneurysm—Insights from Clinical and Experimental Studies - Zain Husain Islam; Hongzhang Mei; Zoe Tetz; Rohan Kanchetty; Sophia Stanisic; Nicholas Hoyt; William Aaron Marcum; Campbell Johnston; Eric William Kent; Mengxue Zhang; Nina Islam; Alvin Anand; et al. (Journal of Vascular Diseases)
Abdominal aortic aneurysm (AAA) is a prevalent vascular disease with high mortality rates upon rupture. AAA features a distinct sexual dimorphism, with a prevalence three times higher in males than in females. Interestingly, females are faced with a greater risk of rupture and a worse prognosis following surgical repairs. Nevertheless, stratified approaches for managing and predicting outcomes of AAA in male and female patients remain limited, largely hindered by our incomplete understanding of the mechanisms underlying this sex dimorphism. In this article, we will summarize the recent clinical and preclinical efforts aimed at understanding the therapeutic and mechanistic implications of sex-specific factors shaping AAA.